IMPROVING THE LEGAL FRAMEWORK FOR EMERGENCY SITUATIONS IS A PRESSING ISSUE OF THE TIME (American Journal of Research in Humanities and Social Sciences, 2025)
This article is devoted to the legal and regulatory documents adopted in our country to protect the population and territories from emergency situations, their socio-historical significance, and their role in the sustainable development of society.